Texture analysis with a time-of-flight neutron strain scanner - Malamud, Florencia (2014)
A time-of-flight (TOF) neutron strain scanner is a white-beam instrument optimized to measure diffractograms at precise locations within bulky specimens, typically along two perpendicular sample orientations. Here, a method is proposed that exploits the spatial resolution (∼1 mm) provided by such an instrument to determine in a nondestructive manner the crystallographic texture at selected locations within a macroscopic object. The method is based on defining the orientation distribution function (ODF) of the crystallites from several incomplete pole figures, and it has been implemented on ENGIN-X, a neutron strain scanner at the ISIS facility in the UK. This method has been applied to determine the texture at different locations of Al alloy plates welded along the rolling direction and to study a Zr2.5%Nb pressure tube produced for a CANDU nuclear power plant. For benchmarking, the results obtained with this instrument for samples of ferritic steel, copper, Al alloys and Zr alloys have been compared with measurements performed using conventional X-ray diffractometers and more established neutron techniques. For cases where pole figure coverage is incomplete, the use of TOF neutron transmission measurements simultaneously performed on the specimens is proposed as a simple and powerful test to validate the resulting ODF.